THE SPIRIT IS WILLING, BUT THE FLESH IS WEAK - Lészai, Lehel (Sacra scripta, 2023)
This is the most intimate prayer of Jesus in Mark’s Gospel. He prayed this right before his capture and there one may sense the struggle of the (divine) man confronting death. In Mk 14,18 he speaks about his resurrection, but he is not facing death easily. Nine of his disciples have to sit down, and three have to accompany him. In Gal 2,9 we read about stulos, and in Mk 3,16-17 Jesus gave new names only to these three disciples, and they wanted to suffer and die with him (Mk 10,38-39;14,29.31). Jesus is troubled facing death, but this is not distrust. The disciples do not make up this story, otherwise it would lack Jesus’s fear, and the fact that they fall asleep. In this story Jesus is stretched to the limit, therefore he needs the companionship of his disciples. He needs the closeness of his disciples, but he needs to be alone with his Father. He is still in hearing range, but who is the one who recorded his prayer. The heart of this passage is his prayer: he wants to escape death, but for him the will of his Father is more important. Jesus returns three times to his disciples, and finds Peter sleeping three times, and then he denies him three times. Jesus remains more and more alone. The prayer is not for escaping the temptation, rather for standing up to the test. The soul may represent the willing spirit as in Ps 51,12), which earlier is identified with the Holy Spirit, or the pneuma means the human spirit (Mk 2,8; 8,12). He warns his disciples, that the body is weak. After his third return they don’t have to stay awake and pray anymore; this is a new situation. Now Jesus knows what God’s will is, and he is ready to die.